Pemanfaatan Jeruedu Sebagai Media Pembelajaran Pada Masa Pandemi Covid-19 di SMPN 19 Bogor - Mirda Yustanto, Rhoma Dhona (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the use of the Jeruedu application as a learning medium for SMPN 19 Bogor students during the pandemic. The research method used is the literature study method in the form of a series of activities related to the method of collecting library data, reading and taking notes, and managing research materials. The results of the study show that Jeruedu has a positive impact which can be seen from the student learning outcomes which are increasing every day through assignments and quizzes. Students' perceptions of subjects carried out Online using the Jeruedu application show that students feel happy using Jeruedu because it is easy and the teacher/educator is not burdensome by giving many assignments, Jeruedu is flexible, that is, easy to access anywhere and anytime, but the weakness of using the Jeruedu application as a learning media that is constrained by internet access from the absence of a data network or smartphones that are used to support all students for the implementation of e-learning learning. In conclusion, the use of the Jeruedu application in subjects has proven effective because it can improve student learning outcomes through planning, process, results and evaluation of student learning. Keywords: Jeruedu application, learning media, Online.